Elaboración de un plan estratégico de marketing para la industria metal mecánica inmenso, en la ciudad de Loja - Uchuari Marizaca, Ericka Janina (2018)
Knowing the great importance of marketing these days, the present work is focused on making a strategic marketing plan for LA INDUSTRIA METAL MECÁNICA INMENSO, due to the fact that they have not done any at present. The main objective of this work is to develop a strategic marketing plan for LA INDUSTRIA METAL MECÁNICA INMENSO, in the city of Loja, with the aim of providing alternative solutions to achieve its positioning in the local market. In order to comply with the aforementioned objective, the research methodology was used to prepare the plan, based on the collection of information from the manager, staff, clients, external and internal factors and variables. Techniques were applied, such as the interview with the manager, the survey of staff and clients, and direct observation to verify the veracity of the information. The main results of the study were: In the internal analysis the marketing variables were analyzed based on direct observation and information provided by the manager, staff and clients of the same, which allowed us to identify their strengths and weaknesses for structuring of the EFI matrix. In the external analysis through the PESTEC analysis, where the factors with the highest incidence are the political and economic factor, with lower incidence the social, technological, ecological and cultural and based on the model of the 5 forces of PORTER, we were allowed to obtain opportunities and threats for the structuring of the EFE matrix. With the information obtained, the high impact SWOT matrix, internal and external matrix or high impact matrix was elaborated and finally the objectives are proposed with their respective strategies for its execution with an action plan. In the final part of the research work, a series of conclusions and recommendations were determined, which allow to determine a synthesis of the research.